2014
DOI: 10.1093/ajh/hpu017
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid X Receptor Agonists Inhibit Hypertension-Induced Myocardial Hypertrophy by Modulating LKB1/AMPK/p70S6K Signaling Pathway

Abstract: RXR agonists prevent the inhibition of the LKB1/AMPK/p70S6K pathway and regulate protein synthesis to reduce LVH. This antihypertrophic effect of bexarotene is independent of blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…LKB1 and p70S6K synergistically regulate the synthesis of critical intracellular proteins and cell proliferation and polarization [56,57]. Our previous study showed that inhibition of LKB1 leads to hypertrophy of cardiomyocytes through up-regulation of p70S6K activity [15]. Consistent with the above findings, the decreased expression and phosphorylation of LKB1 and the increased p70S6K activity in myocardial tissue of DM rats and HG-induced CFs shows that LKB1/p70S6K signaling participates in the development of STZ-induced DCM ( Figure 6).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…LKB1 and p70S6K synergistically regulate the synthesis of critical intracellular proteins and cell proliferation and polarization [56,57]. Our previous study showed that inhibition of LKB1 leads to hypertrophy of cardiomyocytes through up-regulation of p70S6K activity [15]. Consistent with the above findings, the decreased expression and phosphorylation of LKB1 and the increased p70S6K activity in myocardial tissue of DM rats and HG-induced CFs shows that LKB1/p70S6K signaling participates in the development of STZ-induced DCM ( Figure 6).…”
Section: Discussionsupporting
confidence: 77%
“…Multiple previous studies have confirmed that the LKB1/p70S6K pathway plays an important role in the process of pathological cardiac reconstruction. LKB1 and its downstream kinases suppress protein synthesis in cardiac tissues and cardiac fibrosis through down-regulation of p70S6K/ribosomal S6 kinase [15,29]. To investigate the regulatory effect of the RXR agonist on LKB1 and p70S6K activity, we examined the protein levels of LKB1, phosphorylated LKB1 (P-LKB1), p70S6K and phosphorylated p70S6K (P-p70S6K) using immunoblotting.…”
Section: The Rxr Agonist Regulates Activation Of Lkb1 and P70s6kmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a counter cross-talk between AMPKα-Ser 485/491 and AMPKα-Thr 172 [87]. In a further study, Zhu et al (2014) [78] found that ventricular hypertrophy induced by AngII in SHRs might be related to inhibiting LKB1/AMPK activity. But not all the experiments supported this finding.…”
Section: Angii and Ampk In Heartmentioning
confidence: 91%
“…In an isolated heart model study, captopril (an ACEI) did not show the ability that it can phosphorylate AMPK [77]. In another study, in the heart tissue of SHRs, the results showed that activation of AMPK might be unrelated to ACE [78]. Although based on the research of Suarez-Martinez [79], by scoring the staining intensity of AMPK in the heart, AMPK was more abundant in enalapril (an ACEI) treated group while less in the ApoE-deficient control group.…”
Section: Ace and Ampkmentioning
confidence: 94%